The shamans of wall street: a real conundrum in finance. Why systematically poor performing asset managers survive? - Delgado, Francisco A. (2012)
In this paper we propose a behavioral explanation for the survival of poorly performing asset managers. We argue that, in general, asset managers make use of copious amounts of correct but useless information to convince investors about their supposed superior ability to interpret the market. Their marketing skills and motivational speeches seem to be enough to maintain asset managers in business regardless of the results. We present data that show how bad a number of asset managers can be. We also show how prevalent asset managers’ underperformance is. We argue that some Wall Street professionals are able to fool almost all of their clients most of the time into believing that they add value in the services they provide while the data show that this is not true. What we cannot show with this data is whether managers actually believe they are as good as they claim they are, or are not just shamans, albeit shameless as well.